Beyond shoulder arthroplasty: Applications of 3D printed patient-specific instrumentation in shoulder and elbow procedures – a systematic review - Vitor La Banca; Thiago Martins Trece Costa; Ana Victoria Palagi Vigano; Luiz Giglio; Guilherme Henrique Vieira Lima; Joel Murachovsky; Roberto Yukio Ikemoto (Annals of 3D Printed Medicine, 2024)
Purpose: Advancements in 3D printing technology have led to a growing interest on its application in orthopedic surgery. In the context of shoulder and elbow surgery, studies on 3D printing mostly center on surgical guides for the placement of the glenoid component in shoulder arthroplasty, but applications in non-arthroplasty procedures remain unclear. This systematic review aims to evaluate and summarize the literature on the current applications and clinical outcomes of 3D Patient-Specific Instruments (3DPSI) in non-arthroplasty procedures. We expected to find a predominant focus on corrective osteotomies with positive clinical outcomes and minimal complications. Methods: This systematic review adhered to PRISMA guidelines. Eligibility criteria included original research studies presenting primary data on 3DPSI for shoulder and elbow procedures. Exclusions were applied to studies exclusively reporting clinical data on 3DPSI for glenoid component placement in shoulder arthroplasty. A comprehensive literature search was conducted in PubMed/MEDLINE, Scopus, MedNar, Google Scholar, OAIster, and ProQuest Dissertations & Theses. Extracted data included study characteristics, 3DPSI development details, and clinical outcomes. Risk of bias was assessed using MINORS criteria. Results: Out of 845 initially identified records, the final analysis included 20 studies. Regarding the application of 3DPSI, 35 % of the reports addressed cubitus varus osteotomy correction, 30 % focused on clavicle malunion or nonunion, and 15 % centered on corrective osteotomies for proximal humerus malunion. Risk of bias assessment using MINORS criteria demonstrated a mean score of 9.11 out of 16 for studies without a comparator group. Results across different pathologies revealed high patient-reported outcomes (PROs), good patient satisfaction, and minimal complications, which are presented. Conclusion: In non-arthroplasty shoulder and elbow procedures, 3D Printed Patient-Specific Instrumentation have been mostly used for corrective osteotomies and demonstrates overall positive outcomes, low complications, and high patient satisfaction. Advancement in existing knowledge requires robust studies with larger cohorts and comparator groups. Level of Evidence: Level IV. Clinical Relevance: This study, summarizing existing data on 3D Patient-Specific Instruments (3DPSI) in non-arthroplasty shoulder and elbow procedures, offers guidance for future applications and research in this evolving field of orthopedic surgery.